Trans Inheritance Roundtable - Fatima Seedat (African Journal of Gender and Religion (AJGR))
This Roundtable emerges through the first piece submitted for publication by Muneer Abdurouf. Given that the discussion on inheritance for trans individuals is still limited, and the importance of opening this area for discussion, with Abdurouf’s permission, the editors sought responses to the original piece. The responses received reflect a range of perspectives and methodological approaches including the philological and experiential, and South African civil and constitutional law.